Review Of Political Representation Through Representative-Constituent Relations: Case Study Of Members Of The DPR-RI 2014-2019 West Java Electoral District IX PDI-Struggle Faction Maruarar Sirait - Rafifrian Evandio; Chusnul Mar’iyah; Mulyadi Mulyadi (Publikasi Indonesia, 2023)
Political parties play a crucial role as a means of public political participation and are expected to serve as institutions for educating the public about politics. This creates an obligation for political parties to provide political education to the public. This research aims to analyze the role of political parties in implementing political education for the public. The method used is a literature review. Data collection involves studying various secondary sources, including books, scientific journals, expert opinions, and other relevant sources related to the research problem. The analysis is carried out descriptively and qualitatively to elaborate on the research findings. Political parties are organized groups with members who share common goals and values, primarily seeking political power based on their policies. They encourage political participation by seeking and educating the public to engage in political activities. The function of political parties in providing political education to the public aims to enhance the understanding of good political culture among the public. Political parties can collaborate with the public in conducting political education through political socialization, political education, and campaigning. Such political education should help prevent the occurrence of money politics, black campaigns, and vote-buying during elections.